Rhoptromeris haywardi (Blanchard, 1947) is not Rhoptromeris Förster, 1869: new combination in Leptopilina Förster, 1869 (Hymenoptera: Cynipoidea: Figitidae: Eucoilinae) - Reche, Vanina Anadina; Gallardo, Fabiana (Entomological Communications, 2023)
Rhoptromeris haywardi (Blanchard, 1947) is reviewed and the new combination Leptopilina haywardi (Blanchard, 1947) is proposed. Leptopilina haywardi comb. nov. is redescribed and illustrated. Leptopilina Förster, 1869 is cited for the first time for Uruguay and Tephritidae (Diptera) is reported for the first time as its host.